Effectiveness of Continuous Hypertonic Saline in Acute Ischemic Infarcts: A Radiographic and Clinical Evaluation. (16th November 2020) - Chugh, Arunit Jessey S; Shammassian, Berje H; Odetoyinbo, Kolade; Sauer, Adam; Hoffer, Alan S
Abstract: INTRODUCTION: Continuous hypertonic saline has long been used as a form of medical management for reduction of cerebral edema for patients with acute ischemic infarcts. However, the data supporting its use is very limited. Only two other studies–both with small sample sizes–have studied its effects in the literature and neither one showed an improvement in sustained ICP reduction, neurological outcomes, or overall mortality. METHODS: This is an ongoing retrospective review of patients with acute large hemispheric ischemic strokes that were initially managed non-operatively and either treated with continuous hypertonic saline vs routine medical management. Demographics, and baseline comorbidities were collected. Radiographic parameters of cerebral edema (sulcal/cisternal effacement and midline shift) were measured on Computer Tomography (CT) at different time intervals following admission. Similarly, clinical parameters including Glasgow coma scale (GCS), and pupillary changes were collected at each time interval. Lastly, presence/absence of surgery and timing of surgery were collected. T-test correlation was conducted between the continuous variables and chi-square test was conducted between the categorical variables between the two cohorts. RESULTS: Thus far, 50 patients with large acute hemispheric infarcts secondary to MCA or ICA occlusions have been included-30 in the hypertonic group and 20 in the control group. Average age in the hypertonic and control groups was 67 years and 65 years, respectively. Preliminary results indicate there are no significant changes in radiographic progression of cerebral edema, no differences in neurological status, and no differences in the prevention or timing of decompressive hemicraniectomies. CONCLUSION: Continuous hypertonic saline is routinely used for the management of acute hemispheric ischemic infarcts. However, there is essentially no evidence supporting its use. Although transient uses or bolus infusions have been shown to decrease ICP, continuous use has not shown any benefit in several studies with small sample sizes and/or no control groups. Although preliminary, the results of this study demonstrate no differences in radiological or clinical progression, and no effects on timing of surgical decompression.